2019
DOI: 10.1080/00913847.2019.1624658
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the functional movement screen, star excursion balance test and the Beighton score in dancers

Abstract: Usage of any items from the University of Cumbria's institutional repository 'Insight' must conform to the following fair usage guidelines.Any item and its associated metadata held in the University of Cumbria's institutional repository Insight (unless stated otherwise on the metadata record) may be copied, displayed or performed, and stored in line with the JISC fair dealing guidelines (available here) for educational and not-for-profit activities provided that• the authors, title and full bibliographic detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
0
6
0
1
Order By: Relevance
“…The tests for evaluating the left and right functions were conducted from the left in accordance with the basic guidelines [ 20 ]. The lowest score between the two raters was considered the final score [ 34 , 35 , 38 ] ( Table 1 ; Table 2 , Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The tests for evaluating the left and right functions were conducted from the left in accordance with the basic guidelines [ 20 ]. The lowest score between the two raters was considered the final score [ 34 , 35 , 38 ] ( Table 1 ; Table 2 , Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although dance is admittedly different from other sports, it is surprising that the average weekly training load involved in dance is higher than that of football athletes in one season (Rogalski, Dawson, Heasman, & Gabbett, 2013). A study has been conducted and utilized a limited study population using female university contemporary and ballet dancers shown the lack of studies comparing movement assessment tests between various traditional dances of different ethnicities and genders prompted the author to conduct this study (Armstrong, 2020). Over the years, dancers perform repetitive movements to master the skills and quality of their performance (Shah, Weiss, & Burchette, 2012).…”
mentioning
confidence: 99%
“…An imbalance between training load and rehabilitation training results in fatigue and leads to injury (Soligard et al, 2016). A better understanding of injuries and movement analysis for dancers should be conducted to help in the planning and preparation of a systematic training design to prevent overuse injuries (Armstrong, 2020). As stated in a recent study by Armstrong (2020), it is important to examine movement quality and injury risk in dancers of different ethnic backgrounds to determine the level of risk in dance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(47) No se encontró asociación entre la flexibilidad con la prueba de abducción pasiva de cadera y el SEBT, lo que podemos contrastar con un estudio en el cual se realiza la prueba de SEBT con la aplicación de Kinesio Taping, lo que hace aumentar la fuerza muscular en abductores de caderas, eversores de tobillos y aumenta el valor de significancia de la prueba del SEBT con lo que podemos suponer que los resultados de la prueba mejoran en cuanto se aumente la fuerza muscular y con ello el equilibrio en miembros inferiores. (48) McCann con su estudio, afirma que no existen diferencias significativas los puntajes obtenidos entre estudiantes de secundaria y estudiantes universitarios con la prueba del SEBT (49); esto resulta relevante, ya que la data obtenida puede servir como base para futuros estudios con una población del mismo grupo etario para determinar qué cambios se generarán con el paso del tiempo.…”
Section: Interpretación De Los Hallazgosunclassified